ISSUES IN THE SPHERE OF ECOLOGY SAFETY AND RESOURCES FOR THEIR SOLUTION IN THE LIGHT OF POLITICAL ECOLOGY THEORY - V. G. Tyminskiy; L. P. Kurakov; S. M. Pyastolov; M. V. Ignatyev; O. P. Fesenko (Russian Journal of Economics and Law)
Objective: to analyze the world experience of forming the paradigm of political ecology in the aspect of environmental safety.Methods: dialectical method of cognition, detailing, logical generalization.Results: the article formulates conclusions about the topicality of the environmental security issues, confirming in particular by the nature of the changes in consumer demand and environmentally responsible behavior of a certain part of the population. The global trends are identified in the formation and development of international institutions in the field of political ecology, scientific institutes and laboratories working in this field. The analysis of world experience of forming the paradigm of political ecology has shown that currently an attempt is made to introduce nature into the economic relationship as one of their subjects, emphasizing the ambiguous attitude of scientists to ecosystem services.It is revealed that in Russia and abroad the issues of environmental security are studied by a significant number of scientific, educational and public organizations. The most important trends are the shift in emphasis from the natural environment to humans and the systematization and expansion of the list of threats to environmental security.The article also analyzes the main parameters of ecological safety of Russia and formulates conclusions about the poor state of most ecosystems and "ecophobic" industrial infrastructure. Also, the problems of interregional cooperation in the environmental field are defined, as well as the negative impact of transnational corporations on environmental safety. The main tasks of political ecology in the framework of the national program of socio-economic development of Russia are defined. The conclusion is made about the necessity to formulate the problem and describe the principles of a comprehensive program of environmental safety, taking into account the geological security within the national security structure, which, in turn, should be included in a more general program of socio-economic development of Russia.Scientific novelty: the state list of threats to ecological security of Russia is expanded (external threats are studied), and recommendations for improving environmental policies as a component of national security are made.Practical significance: the main provisions and conclusions of the research can be used to determine the main directions of development of the national environmental strategy as a component of socio-economic policy of the country.